What Is a Wireless Sensor Network? - Clyde W. Fraisse; Janise McNair; Thiago Borba Onofre (EDIS)
A wireless sensor network (WSN) is a system designed to remotely monitor and control a specific phenomenon or event. This new 2-page fact sheet discusses the advantages that the WSN has over traditional stand-alone sensors and controllers, power consumption and conservation, and WSN technologies. Written by Clyde Fraisse, Janise McNair, and Thiago Borba Onofre, and published by the UF/IFAS Department of Agricultural and Biological Engineering, January 2018. http://edis.ifas.ufl.edu/ae521